Bridging Intention-Behavior Gap on Green Products Consumption - Waluyo Budi Atmoko; Finisha Mahaestri Noor; Ariefah Yulandari (PT. Publikasiku Academic Solution, 2023)
The issue of green consumerism has been extensively researched, but its impact on the growth of the green product market is small. This happens because intentions that did not manifest in behavior. Emotions had the potential to encourage individuals to carried out the intended behavior. Therefore intentions that reinforced by emotions will soon turn into behavior. The research was conducted with an experimental design. The results show that emotions strengthen the relationship between behavioral intentions to buy and green products buying behavior. Research findings became valuable input for the creation of a green product marketing communication strategy. Giving advertising exposure with emotional appeal was expected to change intention to buy green product to actual purchases